2014
DOI: 10.1293/tox.2013-0048
|View full text |Cite
|
Sign up to set email alerts
|

Calponin Expression in Renal Tubulointerstitial Fibrosis Induced in Rats by Cisplatin

Abstract: Renal tubulointerstitial fibrosis is the common feature of chronic renal failure, regardless of its etiology. Myofibroblasts play important roles in progression of the fibrosis and are characterized by expressions of various cytoskeletons such as vimentin, desmin and α-smooth muscle actin (α-SMA). To pursue the characteristics of the cells, we immunohistochemically investigated the relationship between calponin (a marker of terminal smooth muscles) expression and myofibroblasts in cisplatin-induced rat renal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Cisplatin interferes with DNA replication, increasing DNA damage mainly by forming Ptd(GpG), which promotes cancer cell death (16). However, in spite of cisplatin's established effects for the treatment of cancers, there has been a growing concern that cancer patients have an increased risk of developing lung fibrosis due to cisplatin-induced toxicity (17,18,19). Cisplatin is known to cause renal tubulointerstitial and pulmonary fibrosis in humans (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin interferes with DNA replication, increasing DNA damage mainly by forming Ptd(GpG), which promotes cancer cell death (16). However, in spite of cisplatin's established effects for the treatment of cancers, there has been a growing concern that cancer patients have an increased risk of developing lung fibrosis due to cisplatin-induced toxicity (17,18,19). Cisplatin is known to cause renal tubulointerstitial and pulmonary fibrosis in humans (19).…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of cisplatin's established effects for the treatment of cancers, there has been a growing concern that cancer patients have an increased risk of developing lung fibrosis due to cisplatin-induced toxicity (17,18,19). Cisplatin is known to cause renal tubulointerstitial and pulmonary fibrosis in humans (19). A prior study also showed that chemotherapy with cisplatin or in combination with other cytotoxic agents is correlated with increase in pulmonary fibrosis (20).…”
Section: Introductionmentioning
confidence: 99%
“…The pro-inflammatory cytokines secreted by immune or damaged tubular epithelial cells lead resident fibroblasts turning to active myofibroblast [ 10 - 11 ]. Active myofibroblasts express α-SMA, secrete more collagen I and make other aberrant matrix synthesis and deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Once EMT is induced in renal tubular epithelial cells, it declines E-cadherin expression, induces the expression of fibroblast markers such as vimentin and fibronectin, destroy the tubular basal membrane and transmigrate into renal interstitial spaces [ 12 - 16 ]. Some studies have reported that EMT of tubular epithelium may be involved in cisplatin-induced renal fibrosis [ 11 , 13 , 17 , 18 ]. Cisplatin-elicited ROS stress in damaged epithelial cells and pro-inflammatory cytokines secreted by surrounding immune cells are the possible causes of EMT.…”
Section: Introductionmentioning
confidence: 99%
“…El cisplatino es capaz de causar en el riñón tanto glomeruloesclerosis como fibrosis tubulointersticial (Yu et al, 2016). La fibrosis tubulointersticial es la principal alteración asociada a la insuficiencia renal crónica que se produce tras exposiciones prolongadas al cisplatino (Yuasa et al, 2014), incluso a dosis bajas (Sharp et al, 2016), y que está asociada con un deterioro irreversible de la función renal (Nangaku, 2004). La fibrosis tubulointersticial causa un defecto en la difusión del oxígeno hacia el tejido renal que finalmente conduce al desarrollo de una insuficiencia renal crónica (Katagiri et al, 2016).…”
Section: Fibrosis Tubulointersticialunclassified